2022
DOI: 10.1002/ejp.2066
|View full text |Cite
|
Sign up to set email alerts
|

Association between night pain and quality of life in women: A general population sleep study

Abstract: Background Women with pain present decreased sleep duration and quality of life, but little is known about the consequences of nighttime pain on overall health. Our goal was to compare levels of anxiety, depression and fatigue in women with pain during the night with those without pain. We hypothesized that pain perception is associated with the worsening of fatigue and mood. Methods In total, 244 women aged 20–80 years who took part in the Epidemiologic Sleep Study (EPISONO) met the inclusion criteria, 85 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…Consistent with the results of previous studies (Bjurström et al, 2021;Yu et al, 2022), sleep quality was associated with postoperative pain. The probable cause was that lack of sleep before surgery led to a pronounced rise in mechanical sensitivities following surgery (Haack et al, 2020), and inflammatory processes exacerbated may intensify pain perception (Lucena et al, 2023). In addition, cumulative evidence has demonstrated that the body can become more sensitive to pain and less tolerant of it as a result of poor sleep, which can lead to more severe pain (Wu et al, 2022).…”
Section: Preoperative Sleep Qualitymentioning
confidence: 99%
“…Consistent with the results of previous studies (Bjurström et al, 2021;Yu et al, 2022), sleep quality was associated with postoperative pain. The probable cause was that lack of sleep before surgery led to a pronounced rise in mechanical sensitivities following surgery (Haack et al, 2020), and inflammatory processes exacerbated may intensify pain perception (Lucena et al, 2023). In addition, cumulative evidence has demonstrated that the body can become more sensitive to pain and less tolerant of it as a result of poor sleep, which can lead to more severe pain (Wu et al, 2022).…”
Section: Preoperative Sleep Qualitymentioning
confidence: 99%